Water quality in areas around Galuga Landfill, Bogor Regency, West Java - Yayat Hidayat; Wahyu Purwakusuma; Yusuf, Sri Malahayati; Latief Mahir Rachman; Enni Dwi Wahjunie; Dwi Putro Tejo Baskoro; Aditia Sapto Utomo; Elianah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The research is aimed to analyze leachate, surface water and ground water characteristics around Galuga landfill site, Bogor District. Water samples had been taken in dry season of 2014 and in the end of rainy season of 2015 from several sites in areas around Galuga landfills which included leachate water, surface water, and ground water. Leachate, surface water and ground water had temperature and pH in normal ranges; whereas nitrate and Pb contents were high to very high levels, especially in site adjacent to waste piles. The concentrations decreased in line with increasing distance from waste piles. Higher content of nitrate in leachate occurred in dry season, but in well water it was found in rainy season. Meanwhile, Pb content in well water were high, both in dry and rainy seasons. Concentrations of nitrate and Pb in leachate water were higher than wastewater quality standard, so that the leachate water were not safe to be discharged directly to natural water body. The high content of nitrate and Pb caused the well water unsuitable to be consumed without water treatment processing.